2007
DOI: 10.1111/j.1365-2567.2007.02647.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of human invariant natural killer T subsets in health and disease using a novel invariant natural killer T cell‐clonotypic monoclonal antibody, 6B11

Abstract: Summary Identification of human CD1d‐restricted T‐cell receptor (TCR)‐invariant natural killer T (iNKT) cells has been dependent on utilizing combinations of monoclonal antibodies or CD1d tetramers, which do not allow for the most specific analysis of this T‐cell subpopulation. A novel monoclonal antibody (clone 6B11), specific for the invariant CDR3 loop of human canonical Vα24Jα18 TCR α chain, was developed and used to specifically characterize iNKT cells. In healthy individuals studied for up to 1 year, a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
217
5
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(248 citation statements)
references
References 74 publications
23
217
5
3
Order By: Relevance
“…However, the proportion of CD4 + iNKT cells was not correlated with sex (P = 0.12) or age (P = 0.75). Some of these trends had been observed in previous data sets (24). With a larger sample size, we confirmed the correlations with statistical significance.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…However, the proportion of CD4 + iNKT cells was not correlated with sex (P = 0.12) or age (P = 0.75). Some of these trends had been observed in previous data sets (24). With a larger sample size, we confirmed the correlations with statistical significance.…”
Section: Resultssupporting
confidence: 79%
“…Functional characterization of iNKT cells requires comprehensive assessment of surface expression of homing receptors, lectins, and cell adhesion molecules, as well as cytokine production. Immunoprofiling studies have yet to assay such a comprehensive set of markers in primary iNKT cells in a sufficiently large cohort (18,(20)(21)(22)(23)(24). Here, we profiled iNKT cells in 110 subjects with 19 surface and intracellular markers.…”
Section: Significancementioning
confidence: 99%
“…To our knowledge, this antibody is the only anti-CDR3 idiotype-specific mAb available for a TCR of known specificity. Thus, this novel antibody can be used to specifically identify, enumerate [38] and, as we show here, to localize in tissues, isolate and expand authentic iNKT cells for experimental, diagnostic, and therapeutic studies of human and non-human primate iNKT cells. The availability of multiple reagents active in various assays to identify and for manipulating iNKT cells will enable understanding their role in different patient population subsets (e.g.…”
Section: Discussionmentioning
confidence: 83%
“…It is now widely accepted that the optimal technique for identifying the primary (that is, type 1, invariant) NKT cells is by positive flow cytometric examination with either aGC-loaded CD1d tetramer or the 6B11 mAb, which provide similar specificity. 1,33,46 The three earlier studies linking MDS to NKT cell deficiency used less stringent approaches, including a definition of NKT cells as Va24 þ Vb11 þ CD4ÀCD8À 11 (excluding legitimate CD4 þ NKT cells, which comprised B40% of NKT cells in our study), or Va24 þ CD161 þ cells 12 (excluding legitimate CD161À NKT cells, while including Va24 þ Vb11ÀCD161 þ non-NKT cells). The third study identified NKT cells as Va24 þ Vb11 þ , 10 which usually provides a reasonably accurate approximation of NKT cell frequency, 46,47 despite not necessarily identifying all NKT cells.…”
Section: Discussionmentioning
confidence: 99%
“…1,33,46 The three earlier studies linking MDS to NKT cell deficiency used less stringent approaches, including a definition of NKT cells as Va24 þ Vb11 þ CD4ÀCD8À 11 (excluding legitimate CD4 þ NKT cells, which comprised B40% of NKT cells in our study), or Va24 þ CD161 þ cells 12 (excluding legitimate CD161À NKT cells, while including Va24 þ Vb11ÀCD161 þ non-NKT cells). The third study identified NKT cells as Va24 þ Vb11 þ , 10 which usually provides a reasonably accurate approximation of NKT cell frequency, 46,47 despite not necessarily identifying all NKT cells. 48 Therefore, we suggest a more likely explanation for the discrepancy is that the earlier study pooled results from treated (not with lenalidomide) and untreated patients, whereas we separately assessed the NKT cell frequency of patients before and after treatment with lenalidomide.…”
Section: Discussionmentioning
confidence: 99%